2016
DOI: 10.1590/0104-6632.20160334s20150262
|View full text |Cite
|
Sign up to set email alerts
|

OXYGEN TRANSFER IN THE SOLID-STATE CULTIVATION OF D. monoceras ON POLYURETHANE FOAM AS AN INERT SUPPORT

Abstract: -In recent years, there has been a resurgence of interest concerning solid-state cultivation processes due to a number of advantages over submerged cultivation. However, studies on oxygen transfer and the performance of bioreactors are lacking. Processes that use inert supports loaded with chemically-defined liquid media have several potential applications and offer numerous advantages, such as improved process control and monitoring and enhanced process consistency compared with cultivation on natural solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…According to Musoni et al [96], the bioreactor is the core of biological process. There are four major roles of the bioreactor, which are: In SSF or SMF processes, the bioreactor provides suitable environment for microorganism growth and biological activity [1].…”
Section: Bioreactors For Ssfmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Musoni et al [96], the bioreactor is the core of biological process. There are four major roles of the bioreactor, which are: In SSF or SMF processes, the bioreactor provides suitable environment for microorganism growth and biological activity [1].…”
Section: Bioreactors For Ssfmentioning
confidence: 99%
“…According to Pandey et al [12,13], SSF bioreactor design should carefully consider design and operating variables, especially aeration transfer, temperature control (including cooling system), effective diffusion of oxygen in gas phase and coefficient for heat transfer through bioreactor wall. In SSF, oxygen transfer can often be inefficient in some designs [11,96]. The problems are complicated, affecting the temperature and the water content of the solid medium, which both need to be, controlled tightly [97,98].…”
Section: Bioreactors For Ssfmentioning
confidence: 99%
“…Contrary to the findings of Arora et al (2018) who found that the oxygen consumption rate was directly related to Rhizopus oryzae cell biomass production, the present work showed the impact of the growth phase and the amount of oxygen supply on the growth since they affected the content of oxygen consumption. This was supported by the work of Bastos et al (2016) in which increased biomass and protein production using polyurethane foam as an inert support to increase oxygen transfer, since oxygen uptake affected enzyme production, which was required for fungal growth (Zhou et al, 2018;Abdella et al, 2020).…”
Section: Red Pigment Productionmentioning
confidence: 90%